2022
DOI: 10.3389/fpsyg.2022.872733
|View full text |Cite
|
Sign up to set email alerts
|

What Happened Next? The Experiences of Postsecondary Students With Disabilities as Colleges and Universities Reconvened During the Pandemic

Abstract: COVID-19 caused nearly every college and university in the United States to rapidly shift to remote learning during the spring 2020 semester. While this impacted all students to different degrees, students with disabilities (SWD) faced new challenges related to their mental health, the accessibility of their instruction, the receipt of accommodations, and their interactions with faculty and student support personnel. Literature is emerging that describes the experiences of SWD during the spring 2020 semester a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Our findings align with some of the previous research suggesting that age, gender expression and pre-existing conditions can place some students at risk of experiencing poorer mental health and wellbeing [ 7 , 11 , 12 ]. Our findings also build on existing literature [ 13 ] suggesting that students who identify as gender non-conforming and/or students who identify as homosexual may continue to experience higher levels of mental distress than others.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings align with some of the previous research suggesting that age, gender expression and pre-existing conditions can place some students at risk of experiencing poorer mental health and wellbeing [ 7 , 11 , 12 ]. Our findings also build on existing literature [ 13 ] suggesting that students who identify as gender non-conforming and/or students who identify as homosexual may continue to experience higher levels of mental distress than others.…”
Section: Discussionsupporting
confidence: 91%
“…However, there is wider evidence suggesting that some students were disproportionately impacted. For example, students with disabilities or additional needs were sometimes unable to access their accommodations which lead to varying levels of distress [ 7 , 11 , 12 ]. The disparities in other marginalised communities including sexual and ethnic minority and gender non-conforming groups were also highlighted during the pandemic [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, students diagnosed with LD/ADHD experienced mild levels of depression and stress and moderate levels of anxiety whereas their neurotypical counterparts experienced normal levels of depression, anxiety, and stress. Other studies, similarly, have found negative reactions and concerns stemming from the switch to ERT among students with a variety of disabilities (e.g., Madaus et al, 2022;McMaughan et al, 2021;Zhang et al, 2021). Unplanned ERT creates different and stressful environments for instructors (Hodges et al, 2020;Sari & Nayir, 2020).…”
Section: Discussionmentioning
confidence: 96%
“…Madaus et al. (2022) compared the pandemic‐related experiences of students with disabilities in spring 2020 with their experiences in spring 2021. Participants’ responses related to accessing services and instruction showed no improvement from the spring 2020 semester; further, mental health, motivation to learn, and connections with peers were perceived to be worse in 2021 than in spring 2020.…”
Section: Emotional Costs and Well‐being Among Postsecondary Students ...mentioning
confidence: 99%
See 1 more Smart Citation